Residu Antibiotika pada Hati dan Karkas Ayam Pedaging - Agus Sjafarjanto; Muslihan Huzai (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2014)
This study aims to determine the residue antibiotic on liver and broiler carcass at the market Dukuh Pakis district. Location and time of the research carried out at the Laboratory of Veterinary Public Health Faculty of Veterinary Medicine Wijaya Kusuma University of Surabaya. Sampling by liver and broiler carcass performed in markets around the market Dukuh Pakis district. This study is an observational study, using liver and broiler carcass were taken from a sub market of Dukuh Pakis tested for antibiotic residues were detected comparing the market where the highest levels of antibiotic residues. Samples in the form of livers and broiler carcasses must come from the same broiler taken from the traditional markets and supermarkets around the Dukuh Pakis District. The data obtained were analyzed using descriptive methods.Antibiotic residues on broiler carcasses in Dukuh Pakis market based on the results of the test showed that 27.5% positive and 72.5% negative. While antibiotic residues in broiler liver in Dukuh Pakis Market based testing showed positive results of 32.5% and negative 67.5%.